La incidencia de la formación de grado y la capacitación de las docentes de primero de básica en el desarrollo lógico-maremático en el Centro Educativo "Hazel Mc. Callion". - Ortiz Yánez, Cristina Fernanda (2008)
In the Education Center "Hazel Mc. Callion "the different teacher training among the first teachers of basic non consolidates the teaching and learning on campus. In the center there are two Basic first parallel, one in charge of a licensed nursery and another, a primary school teacher. The way they pose the same content is different, since the learn preschool group playing, manipulating objects and experience while learning, the group of primary teachers is less active working folder filling sheets and designed or repeating memory concepts and has few resources, in the process of learning.